2014
DOI: 10.1007/s00464-014-3443-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for colorectal neoplasia during the clinical learning curve

Abstract: For novices in colorectal ESD, beginning with rectal and smaller lesions may be advisable. Also, using scissors-type knives may increase the R0 resection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…We used the ICC 200 high‐frequency generator (ERBE, Tübingen, Germany). Bowel preparation, details of colorectal ESD procedure, and fixing of resected specimens were described in more detail in our previous report …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the ICC 200 high‐frequency generator (ERBE, Tübingen, Germany). Bowel preparation, details of colorectal ESD procedure, and fixing of resected specimens were described in more detail in our previous report …”
Section: Methodsmentioning
confidence: 99%
“…Although gastric and colorectal ESD share commonality regarding endoscopic techniques, colorectal ESD requires endoscopic maneuverability quite different to that of gastric ESD. We have therefore reported the clinical outcomes achieved by endoscopists who have started to carry out colorectal ESD with no or <5 gastric ESD . Endoscopists who were proficient in colonoscopies and colorectal EMR, and were therefore well aware of the thin wall and endoscopic maneuverability of the colorectum, could safely start to carry out colorectal ESD even without experience in gastric ESD.…”
Section: Introductionmentioning
confidence: 99%
“…100 Indeed, in some series of colorectal ESD performed by novice/trainee endoscopists, all perforations occurred in colonic (nonrectal) cases. 101,102 Learning curves There is no single "learning curve" for ESD, but rather multiple learning curves that vary based on lesion characteristics (eg, anatomic site, size) and outcome of interest (eg, total procedure time, R0 resection rate, adverse event rate). Further, learners with abundant experience assisting in human procedures and/or performing resections in animal models will enter at a higher point on most learning curves and thus experience measurable improvements at a less rapid pace than more novice operators.…”
Section: Training Modelsmentioning
confidence: 99%
“…According to the US National Cancer Database, local excision (LE) is increasingly being performed [1], but local recurrence rate (LRR) was 12 % in T1 tumors [2]. Several studies [3][4][5] regarding endoscopic submucosal dissection (ESD) demonstrated favorable short-term outcomes, and various types of operative procedures for LE have been reported [6][7][8]. However, the optimal local treatment of early rectal cancer (ERC) remains controversial.…”
Section: Introductionmentioning
confidence: 99%